Scientific Approach based E-Module on Vibration, Waves, and Sound Using Canva Design - Wahyuni, Tri; Purwasih, Desy; Syaukani, Mohammad Hafizh; Jumadi (Universitas Pendidikan Ganesha, 2022)
Changes in learning habits during this pandemic have resulted in a decrease in student interest in learning. Teachers have an important role in creating meaningful learning during a pandemic. This research aims to integrate technology in the form of e-modules and use it in learning during the pandemic. The type of research this time is development research with Sadiman's model adapted with Sugiyono's validation. There are 6 stages: analyzing needs, formulating goals, formulating material items, developing media, producing media, and conducting validation and testing. 2 experts carried out validation and the e-module trial were applied to 10 SMP class VIII students. The data obtained will then be analyzed using quantitative descriptive methods. Based on the validation results, material experts obtained an average of 16 in the very good category and validation from media experts obtained an average of 14.5 in the very good category. The results of product trials obtained responses obtained an average tendency of Strongly Agree of 60%. The results show that the contents of the material and content contained in the e-module make students understand the concept, the display of the e-module makes students more motivated to learn. Students find it easier to learn with the e-module because it can be opened anywhere.